Sewer Gas Poisoning: A Report of Two Cases - Ph, Memchoubi; Keisam, Supriya; Kamei, Risilu; Chanu, L Bilasini; Nabachandra, H (Journal of Indian Academy of Forensic Medicine, 2015)
Death associated with confined and enclosed spaces present problem to the investigating pathologist as there may be few or no diagnostic feature at autopsy. In April of 2013, two manual labourers were engaged to clean a sewerage pipe in Imphal by climbing down a manhole. As soon as they entered the manhole, they collapsed and were declared ‘brought dead’ in the hospital. These cases are reported here to highlight an unexpected instance of hydrogen sulphide poisoning in the middle of the city here which was heretofore unheard of in this particular part of the country. H2S is irritant to human tissues causing kerato-conjunctivitis, lacrimation, nasal irritation, dyspnea and coughing at 50-100 ppm. Hydrogen sulphide is quickly absorbed through the lungs and gastrointestinal tracts. The suddenness of the deaths shocked the general public and has served as an eye-opener to the possibility of similar occurrences in the future. Certain precautions are also suggested here to prevent such mishaps.